In Vitro Evaluation of Essential Oils Derived from Piper nigrum (Piperaceae) and Citrus limonum (Rutaceae) against the Tick Rhipicephalus (Boophilus) microplus (Acari: Ixodidae) - Rafaelle Vinturelle; Camila Mattos; Jéssica Meloni; Jeane Nogueira; Maria Júlia Nunes; Itabajara S. Vaz; Leandro Rocha; Viviane Lione; Helena C. Castro; Evelize Folly das Chagas (Biochemistry Research International)
The present research aimed to study the chemical composition and acaricidal activity of Citrus limonum and Piper nigrum essential oils against the cattle tick Rhipicephalus microplus. GC-MS analysis of C. limonum essential oil showed limonene (50.3%), β-pinene (14.4%), and γ-terpinene (11.7%) as the major components; P. nigrum oil was mainly composed of β-caryophyllene (26.2%), σ-ocymene (5.8%), and α-pinene (5.5%). Acaricide activity was evaluated at concentrations of 2.5, 5.0, and 10.0% (v/v) of each plant oil, as well as 1 : 1 combination of both oils (5% : 5%, 2.5% : 2.5%, and 1.25% : 1.25% each), by immersing engorged R. microplus females for one minute. The LC90 of oils from C. limonum, P. nigrum, and the combination were 4.9%, 14.8%, and 5.1%, respectively. C. limonum essential oil caused 100% mortality of engorged females at the highest concentration (10%). P. nigrum essential oil inhibited egg-laying by up to 96% in a concentration-dependent manner, suggesting it reduces tick fecundity. When combined, the oils presented toxicity as to C. limonum oil alone, but with stronger inhibition of oviposition (5% : 5%), indicating a possible additive effect against R. microplus. The present data provide support for further investigation of novel natural products to control bovine tick infestations.